Salavat IUlaev - Protazanov, Yakov (Soviet Union : Soyuzdetfilm, 1940)
A Bashkir national hero, Salavat Yulaev, joins the Pugachev uprising in the 1770s to fight for the freedom of his people against the imperial oppression. The film emphasized a common social enemy of the Bashkirs and the Russians as well as their strong 'brotherly' ties. The script is based on a novel by Stepan Zlobin.
Keywords: Fiction films